”Jag ser till att bli uppfattad som en vanlig DDR-medborgare”: Musikforskaren Gerd Schönfelder, Kungl. Musikaliska akademien och Stasi - Garberding, Petra; Geisler, Ursula; Rosengren, Henrik (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2019)
This article is a case study of the contacts between the music sector in Sweden and the GDR in the 1970s, 1980s and 1990s. The case is the activities of the East-German musicologist and music administrator Gerd Schönfelder (1936–2000) in Sweden at that time, and the debate that arose in the early 1990s when he was accused of having worked for the East German security service, Stasi. The purpose is to provide insight into how music-aesthetic and musicological aspects interacted with politics and ideology in the relations between Sweden and the GDR. In the early 1990s, the availability of material in the Stasi archive was still very limited, and so it was difficult to find out whether it was true that Schönfelder had worked for Stasi, what tasks he had received from the security service and what these tasks meant for his work with Swedish colleagues in the music field. In our article, we try to find answers to these questions by examining how Schönfelder established contact with the Swedish music sector, who were his closest partners in Sweden, and why they were of interest to him. Throughout, we explore Schönfelder’s relationship to Stasi and his work as an ”unofficial employee” for Stasi in Sweden. Finally, we offer a sociological perspective on Schönfelder’s activities in Sweden and the GDR, using Pierre Bourdieu’s concepts of field and capital.